Scientometric Analysis of Islamic Bank in Indonesia - Nadia Nurul Izza (Fara'id and Wealth Management, 2022)
This study aims to identify and map research related to the extent to which the development of Islamic banking research in Indonesia is in scientific literature published by Scopus-indexed journals. The method used is descriptive qualitative using data analyzed from 471 published documents from 1987 to 2022, which were then processed and analyzed using Bibliometric and VOSViewer software to determine bibliometric maps. The results show that the number of articles published by Scopus-indexed journals on the topic of Islamic Banks in Indonesia has grown quite a bit in the early 2010s and will have the potential to continue to grow and increase in line with the increasingly rapid technological developments around the world. In addition, Table 6 provides an overview of the bibliometric review, which shows that some keywords are frequently used, relevant journals, author affiliations, and the author's country. Thus, the results of this study are expected to be developed further, especially in the specific field of Islamic banking.The time frame is limited, and the results are still dynamic. The database used is Scopus. Suggestions for further research can use a better database such as WoS for more comprehensive results. This research can be used as a basic reference to see how the graphical visualization of the development of research trends with the theme of Islamic banking research in Indonesia is published in scientific research so that experts can further develop it.